Prevalence of Anemia and Associated Factors in Pregnant Women Admitted in Antenatal Ward at Birat Medical College Teaching Hospital: An Analytical Cross-Sectional Study - Sharma, Ruby; Shakya, Ayushma; Pokhrel, Sujita; Kc, Heera; Aryal, Neelu (Birat Journal of Health Sciences, 2025)
Introduction: The World Health Organization (WHO) defines anaemia as a condition in which the haemoglobin concentration of a woman during pregnancy is < 11g/dl. Anaemia is one of the global public health problems, with a global prevalence of 29.90% in women of reproductive age and 36.50% in pregnant women.Objectives: The objectives were to find out the prevalence of Anemia and to find out the association between Anemia and selected sociodemographic, obstetric and dietary characteristics of the pregnant women.Methodology: An observational descriptive prospective cross-sectional study was conducted among pregnant women in antenatal ward of Birat Medical College Teaching Hospital from July 2024 to February 2025. Data was collected using a semi structured self-developed questionnaire, entered in MS Excel and converted in to SPSS 25 for statistical analysis. For descriptive analysis mean, standard deviation, range, percentage proportion was calculated. Test of association was done using Chi‑square.Results: In this study, overall prevalence of Anemia was 43.6% (23.9 % are mildly anaemic and 19.7% are moderately anaemic). Prevalence of anaemia was significantly associated with the number of meals per day(p=0.039) and increment of diet in pregnancy than previous (p=0.011)Conclusion: Prevalence of anaemia is quite high despite the iron supplementation signifying Anemia as one of the major health problems among the pregnant women. Screening is essential for timely intervention to reduce maternal and fetal risks.